2010
DOI: 10.1111/j.1365-2702.2010.03264.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies, social support and responsibility in chemical intolerance

Abstract: For improved care, certain coping strategies may be suggested by nurses, the healthcare system needs to provide better social support to these patients and the issue of responsibility for improvement may be discussed with the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…[29,30]. Clinical research on issues such as real or perceived efficacy of treatments [31,32] and assessments of occupational performance of individuals with MCS e.g. [33] were also rejected.…”
Section: Methodsmentioning
confidence: 99%
“…[29,30]. Clinical research on issues such as real or perceived efficacy of treatments [31,32] and assessments of occupational performance of individuals with MCS e.g. [33] were also rejected.…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation regarding coping strategies is that other strategies than those eight assessed in this study may be used in asthma/allergy. The questionnaire used was chosen since it was successfully used in another type of environmental intolerance [31], and since no validated instrument is available for asthma/allergy. Thus, future studies should aim at developing an asthma/allergy-specific questionnaire instrument for coping and social support.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these 21 items was rated on a 7-point scale ranging from "Not at all (0)" to "To a very large extent (6)", identical with the scale for coping strategies. As for the assessment of coping, an almost identical version of this instrument has previously been used to study social support in chemical intolerance [31].…”
Section: Questionnaire Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding coping strategies, one study of MCS/IEI describes prevention/avoidance, detoxification, and emotional self-care as main ways of self-care (Lipson, 2001), and another study has shown avoidance of odorous/pungent environments and asking persons to limit their use of odorous/pungent substances as common strategies (Nordin, Andersson, & Nordin, 2010). With focus on SHR, a longitudinal study by Ternesten-Hasséus, Löwhagen, and Millqvist (2007) has shown that these individuals have reduced quality of life, including social isolation and problems/limitations in paid employment, household work, hobbies, and holidays.…”
mentioning
confidence: 99%